Blood Pressure in Childhood and Adolescence - Hardy, Shakia T (Am J Hypertens, 2021)
Elevated blood pressure (BP) and hypertension commonly occur in children and adolescents and increase the risk of cardiovascular disease in adulthood. The purpose of this review is to summarize recent research in pediatric hypertension including changes in defining hypertension, BP measurement techniques, hypertension epidemiology, risk factors, treatment, and BP-related target organ damage. Defining pediatric hypertension using the 2017 American Academy of Pediatrics’ updated Clinical Practice Guideline resulted in a larger proportion of children being classified as having elevated BP or hypertension compared with prior guidelines. Trends in the distribution of BP among US children and adolescents suggest that BP levels and the prevalence of hypertension may have increased from 2011–2014 to 2015–2018. Factors including a family history of hypertension, obesity, minority race/ethnicity, physical inactivity, high dietary intake of sodium, and poor sleep quality are associated with an increased prevalence of elevated BP and hypertension. Evidence of a linear relationship between systolic BP and target organ damage indicates that BP levels currently considered normal could increase the risk of target organ damage in childhood. Lifestyle changes, such as adhering to the Dietary Approaches to Stop Hypertension diet, are a central component of effectively reducing BP and have been shown to reduce target organ damage. Pharmacologic treatment using angiotensin-converting enzyme inhibitors and angiotensin receptor blockers is an effective and safe method for reducing BP among children with uncontrolled BP after implementing lifestyle changes. Research gaps in the prevention, detection, classification, and treatment of hypertension in children demonstrate opportunities for future study.